Prenatal ultrasonographic diagnosis of limb body wall complex - Thapa, Narayan B; Dangal, Ganesh; Karki, Aruna (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> In this report, a case of limb body wall complex (LBWC) diagnosed by ultrasonography is presented. Limbbody wall complex refers to a rare combination of disruptive and lethal abnormalities which start early in the gestational process. Abnormalities commonly associated with this disorder include cranio-facial abnormalities, scoliosis, ventral body wall defect (thoraco-abdominoschisis), limb deformations, short umbilical cord, and others. Other terms used to describe similar findings include short umbilical cord syndrome, body-stalk anomaly, and amniotic band syndrome. This complex should be distinguished from other body-wall defects including omphalocele and gastroschisis since the prognosis for limb-body wall complex is uniformly poor. The diagnosis of limb-body wall complex can be made by prenatal sonography. Key words: limb body wall complex, abdominal wall defects, amniotic bands, amniotic band syndrome, ultrasonography. doi:10.3126/njog.v2i2.1460 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 72 - 74